HUBUNGAN KONTROL DIRI DENGAN PERILAKU AGRESIF PADA REMAJA DI SMK NEGERI 1 MAUMERE - Pelalgia Sarsadek Baranafe; Margaretha Aprilia Yunarti (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2026)
Aggressive behavior occurring in adolescents, particularly high school students, has been increasing from year to year, both in terms of the number and variety of aggressive behaviors that occur. Cases of aggressive behavior in Indonesia are dominated by adolescents aged 13-17 years old, accounting for 38% of the total victims of violence, totaling 7,451 people. The purpose of this study is to explain the relationship between self-control and aggressive behavior in adolescents at SMK Negeri 1 Maumere. This research is a quantitative study with a correlational analytic design. The sample in this study consisted of 32 students from Class XI TKR3 at SMK Negeri 1 Maumere. Sampling was done using total sampling. The instrument used was a questionnaire. Bivariate data analysis was conducted using the Gamma test. The results of the study showed that the self-control of students in Class XI TKR3 at SMK Negeri 1 Maumere consisted of 1 person in the low category (3.1%), 28 people in the moderate category (87.5%), and 3 people in the high category (9.4%). Aggressive behavior consisted of 2 people in the low category (6.3%), 25 people in the medium category (78.1%), and 5 people in the high category (15.6%). The Gama test results obtained a p-value of 0.037 < ? 0.05, thus Ha is accepted, meaning there is a relationship between self-control and aggressive behavior in adolescents. Based on the research results, it can be concluded that the higher the self-control, the lower the aggressive behavior; conversely, the lower the self-control, the higher the aggressive behavior. Suggestions for SMK Negeri 1 Maumere are that guidance actions need to be carried out so that students have good self-control to minimize the emergence of aggressive behavior. Providing proper guidance services can resolve the problems occurring among students at school.